(untitled) (JOURNAL OF SOCIAL SCIENCE RESEARCH, 2014)
Financial remittances facilitate human capital formation by improving access to education andhealth; an increase in investments and reduction in poverty especially for recipient households. Also, remittancesserve as a critical source of foreign exchange for the national accounts and they promote macroeconomic stability. It has been estimated that remittances are now more than double the size of net official flows, and are second toForeign Direct Investment (FDI) as source of external finance for developing countries. To derive maximum benefitsand forestall the misuse of remittance channels for the purposes of concealing the proceeds of crime, it is crucial toadopt and enforce effective anti-money laundering and counter financing of terrorism measures of acceptableinternational standards. This paper examines the importance of payments and foreign remittances systems; anddrawing lessons from the mutual evaluation of countries in West Africa, concludes that effective and efficientcompliance can only be achieved with a strong commitment of the industry to enforce self regulation. Other measuresto enhance the efficiency of the payments and remittances systems are also recommended.